A Study on a Higher Heating Value of Agricultural Waste in Malaysia - Cindy, Olin; Hassan, Ibrahim; Azri, Alias; Ahmmad Shukrie, Md Yudin; F., Basrawi (2015)
Fuel properties are the fundamental parameters which are often required in order to choose the suitable technology for the combustion process of a fuel. The fuel property focused in this study was higher heating value which is the energy content of agricultural waste. An experimental study was carried out to obtain higher heating value of a few waste samples. The higher heating value was obtained through calorimetric experiment using a bomb calorimeter. The results indicate that coconut husks has the highest heating value with 21.3 MJ/kg while paddy straw has the lowest heating value of 15.6 MJ/kg. Results obtained also have consistent value with other research findings.